Estimation of Water Balance Components for the Watershed of Ghataprabha Sub-Basin - Akshata Bandi H. and Nagraj S. Patil (Nature Environment and Pollution Technology, 2022)
Evaluation of hydrological components in the water balance study is important in planning and maintaining a sustainable watershed to understand the hydrology of the river sub-basin/watershed. This study was carried out to estimate the water balance components in the watershed of the Ghataprabha sub-basin using the hydrological model SWAT (Soil and Water Assessment Tool). The river watershed was further delineated into 35 sub-basins comprising 542 hydrological response units (HRUs). A monthly calibration and validation study has been performed. Statistical model performance indicators, coefficient of determination (R2), and Nash & Sutcliffe (1970) efficiency (NSE) were used to correlate the monthly observed discharge data and monthly simulated discharge data. R2 of 0.75 and NSE of 0.63 for calibration and 0.7 and 0.65 for validation respectively, indicated the satisfactory performance of the model simulation on monthly simulation of flow. Monthly average water balance components (Precipitation, Evapotranspiration, Stream flow, Water yield) were estimated for the watershed.